Evaluasi Aplikasi Muslim Pro untuk Waktu Shalat, Arah Kiblat, dan Keamanan Data - Dinanti, Ayunda Cinta; Bahani, Fadli Nur; Ramzar, Falih Athofa; Nurdjaman, Asep Rudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Muslim Pro is one of the most popular Islamic-based applications among Muslims, providing worship-supporting features such as prayer time calculation, Qibla direction, and a digital Qur'an. However, the accuracy of prayer time calculations and Qibla direction within this application still needs to be evaluated to ensure its reliability. Additionally, data security concerns have arisen due to reports of data breaches involving this application. This study aims to evaluate the accuracy of prayer times and Qibla direction in Muslim Pro and review its data security system. The research employs a qualitative approach using a case study method, collecting data through questionnaires, direct observations, and comparisons with official sources. The findings indicate that while Muslim Pro demonstrates a relatively high level of accuracy in determining prayer times, discrepancies exist when compared to official schedules from Islamic institutions. Furthermore, the Qibla direction feature is prone to deviations due to magnetic sensor interference. Regarding data security, concerns over user privacy persist despite Muslim Pro denying allegations of data breaches. Therefore, updates to the calculation algorithms for prayer times and Qibla direction, along with improvements in privacy policies, are necessary to enhance user trust.